Analisis Kualitas Layanan dan Kepuasan Pasien pada Resep Konvensional Dibandingkan Resep Elektronik di Rumah Sakit A Cibinong Bogor - Feberina, Nona Dian; Hasan, Delina; Widyastuti, Sri (Universitas Malahayati, 2023)
ABSTRACT In the context of implementing health efforts, hospitals must focus on services. Hospital (RS) A is a type C private hospital that has a vision of providing quality and quality health services in order to maintain customer satisfaction. Prescriptions both electronic and conventional provide information about the drug to be given, dosage, route of administration and recommended frequency. Electronic prescriptions are one way to improve the quality of service, by making it easier to receive prescriptions by the Pharmacy Installation so that the services provided are faster. This study aims to determine how patient satisfaction in terms of prescription services with electronic prescriptions. The author uses an observational research design with a cross sectional method supported by a qualitative method by interviewing the pharmacy department by measuring the variables of service quality and patient satisfaction. This study used a sample size of 382 conventional recipes and 382 electronic prescriptions. Based on the results of the study, it was found that there were significant differences in the dimensions of reliability (mean rank 191.5); dimensions of empathy (mean rank 179.11); responsiveness dimension (mean rank 183.94); assurance dimension (mean rank 189.86); dimensions of physical evidence (mean rank 190.47); the dimension of trust (mean rank 175.81); commitment dimension (mean rank 156.85); cost burden dimension (mean rank 153.67); dimension of patient interest (mean rank 156.12); Cooperation dimension (mean rank 171.38). There are significant differences in each dimension of service quality and patient satisfaction in conventional prescriptions and electronic prescriptions at Hospital A where service quality and patient satisfaction in electronic prescriptions give greater results than conventional prescriptions, so it is suggested that electronic prescriptions should always be improved so that there are always improvements. and no longer generate a lot of complaints. Keywords: Electronic Prescription, Pharmacy Services, Quality and Patient Satisfaction. ABSTRAK Electronic Prescription, Pharmacy Services, Quality and Patient Satisfaction. Penelitian ini bertujuan untuk mengetahui bagaimana kepuasan pasien ditinjau dari pelayanan resep konvensional dengan resep elektronik. Penulis menggunakan desain penelitian observasional dengan metode cross sectional didukung dengan metode kualitatif dengan wawancara mendalam dari staff apoteker dan kepala bagian medis, non medis dan keperawatan. Penelitian ini menggunakan besaran sample 382 resep konvensional dan 382 resep elektronik. Berdasarkan hasil penelitian diperoleh hasil bahwa terdapat perbedaan secara signifikan pada dimensi realibilitas (mean rank 191,5); dimensi empati (mean rank 179,11); dimensi daya tanggap (mean rank 183,94); dimensi jaminan (mean rank 189,86); dimensi bukti fisik (mean rank 190,47); dimensi kepercayaan (mean rank 175,81); dimensi komitmen (mean rank 156,85); dimensi beban biaya (mean rank 153,67); dimensi ketertarikan pasien (mean rank 156,12); dimensi kerjasama (mean rank 171,38). Terdapat perbedaan yang signifikan disetiap dimensi kualitas layanan dan kepuasan pasien pada resep konvensional dan resep elektronik di RS A dimana kualitas layanan dan kepuasan pasien pada resep elektronik memberikan hasil yang lebih besar dibandingkan resep kovensional, sehingga disarankan harus selalu ditingkatkan untuk resep elektronik agar selalu terdapat perbaikan dan tidak lagi menghasilkan banyak komplain. Kata Kunci: Resep Elektronik, Pelayanan Farmsi, Kualitas dan Kepuasan Pasien.